If you are good at arithmetic sequences in math please help I am giving more points
![If you are good at arithmetic sequences in math please help I am giving more points class=](https://us-static.z-dn.net/files/d96/d3c96e90d924d6a37ff74adbdd8913e3.png)
Answer:
[tex]a_n=-5n+106[/tex]
Step-by-step explanation:
Arithmetic sequences are linear.
Let's find the slope.
[tex]\frac{a_{16}-a_{7}}{16-7}=\frac{26-71}{16-7}=\frac{-45}{9}=-5[/tex].
So the slope is -5.
We know this about our equation:
[tex]a_n=-5n+b[/tex]
We need to find [tex]b[/tex].
Let's use a point on the line like [tex](7,71)[/tex].
Input the point into our equation:
[tex]71=-5(7)+b[/tex]
[tex]71=-35+b[/tex]
Add 35 on both sides:
[tex]106=b[/tex]
The equation for this line/arithmetic sequence is:
[tex]a_n=-5n+106[/tex].
Answer:
[tex]a_{n} =101+(n-1)(-5)[/tex]
Step-by-step explanation:
Let's start by finding the common difference of this arithmetic sequence.
The change from [tex]a_{7}[/tex] to [tex]a_{16}[/tex] is -45 because it decreased 45.
[tex]a_{16}[/tex] is 9 terms away from [tex]a_{7}[/tex].
If we divide the change by the difference in n, then we can find the difference between each term, or the common difference.
-45/9 = -5, so the common difference is -5.
Now, we want to find [tex]a_{1}[/tex].
We can do this using the common difference. Subtracting the common difference from [tex]a_{7}[/tex] six times should tell us what [tex]a_{1}[/tex] is, so let's do that.
[tex]a_{1}[/tex] = 71 - (-5) - (-5) - (-5) - (-5) - (-5) - (-5)
A reminder, subtracting a negative is basically the same as adding it.
[tex]a_{1}[/tex] = 71 + 5 + 5 + 5 + 5 + 5 + 5
[tex]a_{1}[/tex] = 101
With the common difference and [tex]a_{1}[/tex], we now have all the parts we need to write a rule for the nth term of this sequence.
The formula for the nth term of a sequence is
[tex]a_{n} =a+(n-1)d[/tex], with [tex]a_{n}[/tex] being the nth term, a being [tex]a_{1}[/tex], and d being the common difference.
We can just substitute the common difference and a to get our formula.
[tex]a_{n} =101+(n-1)(-5)[/tex]